PERBANDINGAN SIFAT OPTIK CDOTS BERBAHAN DAUN BINAHONG (ANREDERA SCANDES L.) SEGAR DAN KERING MENGGUNAKAN METODE BOTTOM UP - Yuliana Sri Asmara; Anggita Rizki Maharani; Lais Shifa Aulia; Irnin Agustina Dwi Astuti (Universitas Tanjungpura, 2022)
Carbon dots (Cdots) are synthesizable nanoparticles. One of them is taking advantage of binahong leaves (Anredera scandes L.). In this research, the synthesis of Cdots fresh binahong leaves and dried binahong leaves has been carried out. Using buttom up method and UV-Vis characterization. Microwave heating for 30 minutes. Meanwhile, the physical properties of the resulting Cdots color are fresh Binahong leaves showing a yellowish green color, while the physical properties of dry Binahong leaves show a brownish green color. Cdots fresh binahong leaves has a light absorbance spectrum at a wavelength of 200-800 nm with the highest intensity measured at a wavelength of 323 and the energy value of the band gap of 1.503 Ev. Meanwhile, for Cdots, dried Binahong leaves have a light absorption spectrum at a wavelength of 200-800 nm with the highest intensity measured at a wavelength of 361 nm and an energy value of 8.231 Ev band gap.